Infiltrative thyrotoxicosis: an unusual case of diffuse large B cell lymphoma - McCarthy, Michael T (Oxf Med Case Reports, 2016)
Thyrotoxicosis is most commonly caused by Graves’ disease, toxic multinodular goitre, a functioning thyroid adenoma, or thyroiditis. Extrinsic infiltrative conditions affecting the thyroid gland are typically destructive, and associated with thyroid hypofunction. We describe the case of a 61-year-old woman who presented to our hospital with symptoms of thyrotoxicosis, neck swelling and thyroid function tests consistent with hyperthyroidism. An ultrasound revealed a multinodular goitre with retrosternal extension, but CT imaging suggested thyroid gland infiltration, with cervical lymphadenopathy. An excisional lymph node biopsy confirmed the diagnosis of diffuse large B cell lymphoma causing infiltrative thyrotoxicosis. Treatment with six cycles of Rituximab-CHOP lead to rapid normalization of symptoms, imaging, and thyroid function.